Strategy to manage T-Wave Oversensing in a Biventricular ICD - Mohammad Ali Akbarzadeh; Mohammad Hassan Namazi; Morteza Safi; Mehdi Sheibani (Publisher: Shahid Beheshti University of Medical Sciences, 2017)
T-wave oversensing is a relatively prevalent cause of intracardiac signals oversensing in patients with Implantable Cardioverter Defibrillator (ICD). Some of these oversensings are typically corrected with device reprogramming. If reprogramming fails to resolve the issue, invasive options such as repositioning the implanted lead may be necessary. We present a patient with dilated cardiomyopathy and intermittent T wave oversensing by a cardiac resynchronization therapy (CRT) that was managed by altering V-V timing.